2009
DOI: 10.1093/rpd/ncn318
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of oral and intraperitoneal administration of CBMIDA for removing uranium in rats after parenteral injections of depleted uranium

Abstract: The efficacy of oral administration of the chelating agent catechol-3,6-bis(methyleiminodiacetic acid) (CBMIDA) for removing uranium from rats after intraperitoneal (i.p.) and intramuscular (i.m.) injections of depleted uranium (DU) was examined and the results with those by the i.p. injection of CBMIDA were compared. In Experiment 1, after a single i.p. injection of 8 mg kg(-1) of DU of rat's body weight, 35 8-week-old male rats were divided into seven groups consisting of five rats each. Three groups were ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 27 publications
0
8
0
1
Order By: Relevance
“…25 Nevertheless, oral administration has the advantage of being the most simple treatment irrespective of place and time, and the patients can receive long-term treatment without pain caused by parenteral administration. 26 In this study the oral administration of HER showed a high efficacy in nude mice bearing human tumors. This strongly suggests that HER would be a more attractive industrial product for medicinal foods as well as pharmaceutical products.…”
Section: Resultsmentioning
confidence: 68%
“…25 Nevertheless, oral administration has the advantage of being the most simple treatment irrespective of place and time, and the patients can receive long-term treatment without pain caused by parenteral administration. 26 In this study the oral administration of HER showed a high efficacy in nude mice bearing human tumors. This strongly suggests that HER would be a more attractive industrial product for medicinal foods as well as pharmaceutical products.…”
Section: Resultsmentioning
confidence: 68%
“…8,14 Oral administration has been the most simple treatment of anticancer drugs, irrespective of time and place, and long-term treatment without patients' pain caused by parental administration. 8,32 In this study, the oral intake of LSGE showed a high efficacy in suppressing tumor metastasis. Therefore, LSGE could be considered a nontoxic antitumor supplement for inhibition of metastasis as well as for growth inhibition of tumors.…”
Section: Resultsmentioning
confidence: 71%
“…For the treatment of DU intoxication, scholars mainly focused on DU decorporation in the body using synthetic chelating agents, and a series of agents have been developed910111213. However, there are few drugs with low toxicity that are highly effective in promoting the excretion of DU.…”
mentioning
confidence: 99%